Aplikasi Pinjaman Pembayaran Secara Kredit Pada Bank Yudha Bhakti - Hasan Abdurahman; Asep Ririh Riswaya (Jurnal Computech & Bisnis (e-Journal), 2014)
Payments on credit applications in Bank Yudha Bhakti is a company engaged in the savings, lending and payments serve customers, especially in the areas of savings and loan services, payment for which the management data is still using semi-computerized, so that customers will make the deposit, lending and payment takes long enough in because of customer service, especially in the field of payment is not fast. By this is expected to help the company to improve service customers as well as to store data or other important documents that should be kept well so that in the presentation of information to be fast and accurate. Method of payment credit application development created using waterfall method with system development tools such as Object Oriented Analysis System (OOAD), use case diagrams, flow of events, relations actor, and activity diagrams. As well as data collection techniques by observation, interview and literature study. Implementation of the program using the programming language Visual Basic 6.0, the database using Access. This credit payment applications that are designed to build a computerized application system making it easier for companies to manage customer data loan data, deposit data, payment data. Keywords: customer data; loan data; data storage; payment data